Christ’s Supremacy: Colossians 1:15-20 and Its Implication in Education - Chandra Han (Universitas Pelita Harapan, 2019)
Supremacy of Christ in Col. 1:15-20 is essential to Christian faith. Many attempts have been made to examine this passage and mostly from the theological point of view. The aim of this article is to reexamine this passage and propose an analysis from the perspective of Christian education (with the implications) by firstly exegeting the passage in Colossian’s context. The exegesis begins with providing the translation form the Greek text, proposing the structure followed by demonstrating the critical issue in each section of the structure, and finally summarizing the principles. The next step is to demonstrate the analysis from the perspective of Christian education on every section in the structure, followed by the significance of this passage in Christian education.